Photocatalytic composite material, preparation method and application of photocatalytic composite material in coating
Through the semiconductor-semiconductor interlaced heterojunction structure and zeolite support of bismuth oxychloride and titanium dioxide composition, combined with mechanical dispersion and high-speed oscillation technology, the high temperature and high pressure and organic solvent use problems of existing photocatalytic material preparation methods are solved, and the problem of high temperature and high pressure and organic solvent use is improved. Photocatalytic properties and coating functions.
Patent Information
- Application Number
- CN202310823414.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-10
AI Technical Summary
The existing preparation methods for photocatalytic materials usually require high temperature and high pressure conditions or the use of organic solvents, and the photocatalytic performance of anatase titanium dioxide is insufficient when used in coatings, which affects air purification and antibacterial and antiviral functions.
The composition of bismuth oxychloride and titanium dioxide is prepared by a semiconductor-semiconductor interlaced heterojunction structure, combined with a zeolite carrier and reasonable additives, and mechanical dispersion and high-speed oscillation process under normal temperature and pressure conditions, avoiding the use of organic solvents.
It improves the visible light photocatalytic performance of photocatalytic materials, reduces side effects on the coating film, enhances the formaldehyde and toluene purification functions, and imparts the coating air purification and antibacterial and antiviral functions.
Smart Images

Figure CN119281353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalysis, and in particular to a photocatalytic composite material, a preparation method and application thereof in coatings. Background Art
[0002] Photocatalytic technology is a clean technology that uses solar energy to degrade organic pollutants. Under the action of light, the photocatalyst produces a strong catalytic degradation function, and eventually degrades harmful substances into carbon dioxide and water. Nano-titanium dioxide is a widely used photocatalytic material and is currently one of the most ideal materials for controlling indoor environmental pollution in the world. The mechanism of action of nano-titanium dioxide photocatalyst is essentially a redox reaction. The principle diagram of its mechanism of action is shown below. Figure 2 .
[0003] When it is irradiated by light with a wavelength of ≤387.5nm, the electrons in the valence band will be excited, crossing the forbidden band into the conduction band, and at the same time, corresponding holes will be generated in the valence band. Unlike metal conductors, there is a lack of continuous regions between the energy bands of semiconductors. The conduction band electrons and valence band holes (also called photoelectrons and photoholes) generated by light excitation have sufficient lifespan before recombination. Under light irradiation, photocatalysts can absorb energy below the band gap energy, causing their surface to be excited and generate electrons (e - ) and holes (h + ). These electrons and holes have strong reduction and oxidation capabilities, and can react with water or contained oxygen to produce hydroxyl radicals and super anion ions. The oxidation energy of these holes and hydroxyl radicals is greater than 120kcal / mol, and they have strong oxidation ability, which can cut and decompose almost all chemical bonds that constitute organic molecules. Therefore, various harmful chemicals and odorous substances can be decomposed or harmlessly treated to achieve the effect of purifying the air, anti-pollution and deodorization. Nano titanium dioxide materials also have some disadvantages. For example, titanium dioxide has a wide band gap and must be illuminated by ultraviolet light to stimulate good photocatalytic performance, and the utilization rate of sunlight is low; nano titanium dioxide has the characteristics of high specific area, which makes it highly active. When used directly in the coating, it often produces certain oxidative side effects on the organic components in the coating, and the coating shows discoloration, powdering, poor aging resistance and other problems in the macroscopic view; affected by the complex components in the coating, the photocatalytic performance of nano titanium dioxide will be greatly discounted after it is directly applied in the coating, and it will directly affect the functionality of the coating, such as air purification, antibacterial and antiviral functions.
[0004] Bismuth oxychloride is an important ternary semiconductor compound with excellent electrochemical properties. The crystal structure of bismuth oxychloride is Pb FCl type, belonging to the tetragonal system, and can be regarded as a layered structure composed of double [Cl] ion layers and [Cl-Bi-O-Bi-Cl] layers arranged alternately along the (001) direction. As a new type of photocatalyst developed in recent years, bismuth oxychloride has different bandgap widths due to different preparation processes and material morphologies. Literature reports that the bandgap width of bismuth oxychloride is about 3.19 to 3.6 eV, and its photocatalytic performance can usually only be manifested under ultraviolet light excitation conditions.
[0005] There have been many reports on the enhancement of photocatalytic materials by using bismuth oxychloride and titanium dioxide materials. The enhancement modification methods for bismuth oxychloride usually include the following: 1) alloying; 2) defect introduction; 3) morphology control; 4) bismuth-rich strategy; 5) heterojunction construction. The heterojunction is constructed by combining BiOCl and a semiconductor with a matching band structure, which can not only broaden the light absorption range of BiOCl, but also effectively inhibit the recombination of electrons and holes. For example, BiOCl-C3N4, pn-type BiOCl@CeO2 (cerium oxide), Z-type Bi3O4Cl / BiOCl, etc.
[0006] Common methods for constructing heterojunctions include traditional solvothermal method, sol-gel method and co-precipitation method, etc. These methods usually use some high temperature and high pressure conditions, or use some organic solvents, such as Wang Lei [1] et al. prepared BiOCl / TiO2 composite materials by traditional solvothermal method. Bi(NO3)3·5H2O (2mmol) and NaCl (2mmol) were mixed, 60mL of deionized water was added, stirred vigorously for 10 minutes, pH was adjusted with NaOH, and then stirred thoroughly for 1 hour. The mixture was transferred to a 100mL autoclave and kept at 160℃ for 24h; Liu Xiaoyu [2]The BiOCl / TiO2 composite material was prepared by coprecipitation. Different proportions of tetrabutyl titanate Ti(OCTi(OC4H9)4 and 2.7g BiCl3 powder were added to 1mol / L 100ml HCl solution in sequence. Then 1.0g / L SDBS dispersant was added to the solution and stirred continuously for 10 minutes until a transparent solution was formed. Then, an ammonia solution was added dropwise to the mixture under magnetic stirring, and the pH value was adjusted to 9 to ensure complete precipitation. The suspension was stirred continuously for 30 minutes at room temperature, and the resulting precipitate was separated by centrifugation and washed repeatedly with deionized water and ethanol several times. Finally, the precipitate was dried at 60°C for 8 hours, ground and calcined at 400°C in a muffle furnace for 2 hours, heated at 10°C / min, and cooled to 100°C in 2 hours. The powder was ground and screened to obtain TiO2 / BiOCl composite catalyst powders with weight ratios of 5%, 10%, 15%, 20%, 25%, and 30%, respectively. Dalia Sánchez-Rodríguez et al. [3] BiOCl / TiO2 composites were prepared by sol-gel method. First, a suspension of ethanol (5.5 mL), deionized water (5.5 mL) and BiOCl sample was prepared under continuous stirring. Subsequently, 1 mL of titanium isopropoxide Ti(OCH(CH3)2)4 solution and 4.5 mL of anhydrous ethanol were added dropwise to form a gel. The gel was placed in an oven in a closed bottle at 80 °C for 24 h. Subsequently, the samples were washed with ethanol and dried at 110 °C, and finally they were calcined at 450 °C for 4 h with a heating ramp of 5 °C min -1 . It is not difficult to find from the examples in the above literature that in the preparation process of bismuth oxychloride and titanium dioxide composite materials, whether it is a solvothermal method, a coprecipitation method or a sol-gel method, some high temperature and high pressure conditions will be used, or some organic solvents such as alcohols will be used. These preparation methods have strict and harsh conditions, the preparation process takes a long time, and the use of organic solvents is not environmentally friendly.
[0007] The relevant quotes described above are as follows:
[0008] [1] Wang Lei, Kang Kai, Han Hao, et al. Preparation and photocatalytic properties of BiOCl / TiO2 composite materials[J]. Water Treatment Technology, 2022, 48(02): 76-79+92. DOI: 10.16796 / j.cnki.1000-3770.2022.02.016.
[0009] [2] Liu Xiaoyu. Preparation of TiO2 / BiOCl composite catalyst and study on its photocatalytic degradation performance[D]. North China University of Water Resources and Electric Power, 2016.
[0010] [3] Sánchez-Rodríguez D, Medrano MGM, Remita H, et al. Photocatalytic properties of BiOCl-TiO2 composites for phenol photodegradation[J]. Journal of environmental chemical engineering, 2018, 6(2): 1601-1612.
[0011] Chinese invention patent CN105771952 A mentions: In an ice-water bath, 37% hydrochloric acid, water, and tetrabutyl titanate are mixed in a volume ratio of (0.6-1.3): 100:10, stirred for reaction for 2 hours, and aged at room temperature to obtain a titanium dioxide sol. The powdered photocatalytic material is added to the solvent, and the powdered material microsol is obtained after ultrasonic dispersion; the titanium dioxide sol is mixed with the powdered photocatalytic material microsol, and the dispersion is uniform to obtain a powdered titanium dioxide mixed sol; the powder-titanium dioxide mixed sol is sprayed on a carrier substrate at 80°C, and a film is coated by spraying, and then dried at room temperature.
[0012] Chinese invention patent CN112920663 A mentions: Disclosed is an antifouling self-cleaning coating and a preparation method thereof, wherein the antifouling self-cleaning coating comprises a hydrophobic material, a photocatalytic material and an aqueous emulsion, and the photocatalytic material comprises one or more of C3N4, doped C3N4, composite C3N4 and nano-bismuth oxide.
[0013] Chinese invention patent CN103464183 A mentions: A method for preparing titanium dioxide / bismuth oxychloride nano photocatalyst powder is disclosed, which is characterized in that it is a method for preparing rutile titanium dioxide / bismuth oxychloride nano photocatalyst powder by one-step synthesis of rutile phase titanium dioxide / bismuth oxychloride nano photocatalyst powder using precursors of chrysene and chrysene under low temperature conditions. The method comprises: adding a bismuth-containing titanium compound to an alcohol solvent to form a titanium precursor with a concentration of 0.1 to 20 mol / L, adding a bismuth-containing compound to the formed titanium precursor and continuing to stir, then adding distilled water, the volume ratio of deionized water to alcohol is 1:1 to 5, stirring evenly, sealing and placing in an oven, standing at a temperature of 30 to 80°C, washing with water after 12 to 72 hours, and drying at 30 to 80°C to obtain rutile phase titanium dioxide / bismuth oxychloride nano photocatalyst powder with a particle size of 20 to 800 nm.
[0014] Chinese invention patent CN 113751033 A mentions: A method for preparing a MOF-modified zeolite-loaded BiOX / TiO2 photocatalytic material is disclosed, wherein the method for preparing the photocatalytic material is: adding KX to a mixed solution of deionized water and anhydrous ethanol, stirring for 20 minutes, adding TiO2 in a ratio of n(BiOX):n(TiO2)=0.01-100, stirring evenly, and then adding Bi(NO3)3·5H2O to an ethylene glycol solution, stirring evenly, adding MOF-modified zeolite, transferring the mixed solution to a high-pressure reactor, heating to 120-250°C for reaction for 12-36 hours, cooling to room temperature, centrifuging the obtained precipitate, and washing it alternately with anhydrous ethanol and distilled water for several times, and vacuum drying at 80°C to obtain the finished product.
[0015] As mentioned above, there are many related public technologies for the preparation of photocatalytic materials. However, the preparation methods or processes of these photocatalytic materials are relatively complicated and have the following problems:
[0016] Problem 1: The method of constructing a titanium dioxide and bismuth oxychloride heterojunction usually requires certain special processes and conditions, such as high temperature and high pressure conditions; or the use of organic solvents such as alcohols, which are not environmentally friendly.
[0017] Problem 2: Due to the limitations of the conductive structure of the material, anatase titanium dioxide usually has poor visible light photocatalytic performance and usually has certain side effects on the coating, which limits its application in photocatalytic coatings.
[0018] Problem 3: When anatase titanium dioxide photocatalytic materials are used in coatings, their photocatalytic performance will be greatly reduced due to the complex components in the coatings, which will ultimately affect the functionality of the coatings, such as antibacterial and antiviral properties. Summary of the invention
[0019] In order to solve the problems in the prior art mentioned above, the present invention provides a photocatalytic composite material, a preparation method and its application in coatings. The preparation process of the photocatalytic material of the present invention is simple and environmentally friendly, can improve the visible light photocatalytic performance of the photocatalytic material in the coating, and at the same time can reduce the side effects of the photocatalytic material on the coating film.
[0020] To solve the above problems, the present invention is implemented through the following technical solutions:
[0021] The first invention object of the present invention is:
[0022] Provided is a photocatalytic composite material, comprising a bismuth oxychloride / titanium dioxide composition having a semiconductor-semiconductor staggered heterojunction.
[0023] The photocatalytic composite material of the present invention is further optimized as follows:
[0024] The bismuth oxychloride / titanium dioxide composition comprises the following components:
[0025] Bismuth oxychloride, titanium dioxide, dispersant, defoamer, stabilizer, thickener and deionized water.
[0026] The photocatalytic composite material of the present invention is further optimized as follows:
[0027] The bismuth oxychloride / titanium dioxide composition comprises the following components in parts by weight:
[0028] 1-30 parts of bismuth oxychloride, 1-30 parts of titanium dioxide, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-5 parts of stabilizer, 0.1-2 parts of thickener, and the rest is supplemented to 100 parts with deionized water.
[0029] The photocatalytic composite material of the present invention is further optimized as follows:
[0030] The stabilizer is one or a combination of zeolite and clinoptilolite; the microstructure of the stabilizer is a nanorod structure with a width of 100-500nm and a length of 200nm-5μm.
[0031] The photocatalytic composite material of the present invention is further optimized as follows:
[0032] The dispersant is one or a combination of nonionic surfactants or anionic surfactants.
[0033] The photocatalytic composite material of the present invention is further optimized as follows:
[0034] The bismuth oxychloride is an ultra-thin nanosheet structure, and the thickness of the nanosheet is 5 to 100 nm.
[0035] The photocatalytic composite material of the present invention is further optimized as follows:
[0036] The crystal form of the titanium dioxide is anatase or rutile, and the particle size of the titanium dioxide is 2 to 50 nm.
[0037] The photocatalytic composite material of the present invention is further optimized as follows:
[0038] The stabilizer is one or a combination of zeolite and clinoptilolite;
[0039] The microstructure of the stabilizer is a nanorod structure with a width of 200-400nm and a length of 500nm-3μm.
[0040] The photocatalytic composite material of the present invention is further optimized as follows:
[0041] The dispersant is one or a combination of polycarboxylic acid sodium salt, polyacrylate ammonium salt or phosphate ester.
[0042] The photocatalytic composite material of the present invention is further optimized as follows:
[0043] The bismuth oxychloride is an ultra-thin nanosheet structure, and the thickness of the nanosheet is 10-30nm.
[0044] The photocatalytic composite material of the present invention is further optimized as follows:
[0045] The crystal form of the titanium dioxide is anatase or rutile, and the particle size of the titanium dioxide is 5 to 10 nm.
[0046] The second object of the present invention is:
[0047] A method for preparing the above-mentioned photocatalytic composite material is provided, which comprises the following preparation steps:
[0048] A. Add dispersant, defoamer, stabilizer and thickener into deionized water, stir at a speed of 400-800 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0049] B. adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 400-800 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the materials and subjecting them to a high-speed shaking process for 0.5-2 hours;
[0050] The mass ratio of the material before adding zirconium beads to the mass ratio of zirconium beads is selected between 1:1 and 1:5, and the size of the zirconium beads is selected between 0.6 and 1.0 mm;
[0051] C. Filter the above solution using ash-free filter paper to remove the zirconium beads, collect the filtrate to obtain a photocatalytic composite slurry, and finally obtain a bismuth oxychloride / titanium dioxide composition with a semiconductor-semiconductor staggered heterojunction.
[0052] The third invention object of the present invention is:
[0053] Provided is a coating, which comprises the above-mentioned photocatalytic composite material.
[0054] The fourth invention objective of the present invention is:
[0055] The application of the above-mentioned photocatalytic composite material in air purification and / or antibacterial and / or antiviral.
[0056] The fifth invention objective of the present invention is:
[0057] The above-mentioned coating is used in air purification and / or antibacterial and / or antiviral applications.
[0058] The photocatalytic composite material of the present invention uses titanium dioxide nanoparticles and bismuth oxychloride nanosheets through a zeolite carrier with a special nanorod structure, supplemented by reasonable auxiliary agents and a simple preparation process, to obtain a titanium dioxide-bismuth oxychloride composite photocatalytic material. The preparation process of the photocatalytic composite material of the present invention is simple and environmentally friendly, and only requires a simple pre-dispersion and high-speed oscillation process under normal temperature and pressure conditions, and no organic solvent is added during the preparation process.
[0059] The titanium dioxide-bismuth oxychloride composite photocatalytic material prepared by the present invention can effectively improve the visible light photocatalytic performance of the material through the synergistic effect of the two photocatalytic materials; the porous characteristics of the stabilizer zeolite can also improve the formaldehyde and toluene purification function of the material (see Comparative Example 1); the selection of a suitable dispersant (see Comparative Example 2) and a preparation process (see Comparative Example 3) can effectively improve the stability of the material.
[0060] After the composite photocatalytic material of the present invention is used in the coating, it can effectively reduce the side effects of rutile titanium dioxide on the coating film (Comparative Example 5), such as powdering or discoloration, and after being used in the coating, the visible light photocatalytic performance of the coating can be verified; after being used in the coating, it can give the coating the functions of air purification (especially degradation of benzene series), antibacterial and antiviral. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The present invention is a flow chart of the steps for preparing the photocatalytic composite material.
[0062] Figure 2 This is a schematic diagram of the mechanism of action of nano-titanium dioxide photocatalyst. DETAILED DESCRIPTION
[0063] In order to make the application, technical scheme and advantages of the present invention clearer, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not limited to the present invention. All simple improvements to the preparation method of the present invention under the premise of the present invention are within the protection scope of the present invention.
[0064] Example 1
[0065] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0066] 5 parts of bismuth oxychloride, 22 parts of titanium dioxide, 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 2 parts of clinoptilolite stabilizer, 0.3 parts of acrylic thickener, and the rest is supplemented to 100 parts with deionized water.
[0067] Preparation method of the photocatalytic composite material of this embodiment:
[0068] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0069] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads is selected to be 1.0 mm;
[0070] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0071] Performance Testing:
[0072] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0073] Example 2
[0074] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0075] 12.5 parts of bismuth oxychloride, 20 parts of titanium dioxide, 0.1 parts of polyacrylate ammonium salt dispersant, 0.1 parts of mineral oil defoamer, 0.5 parts of zeolite stabilizer, 0.2 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0076] Preparation method of the photocatalytic composite material of this embodiment:
[0077] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0078] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.7 mm;
[0079] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0080] Performance Test:
[0081] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0082] Example 3
[0083] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0084] 15 parts of bismuth oxychloride, 10 parts of titanium dioxide, 0.5 parts of phosphate dispersant, 0.5 parts of silicone defoamer, 0.5 parts of clinoptilolite stabilizer, 1 part of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0085] Preparation method of the photocatalytic composite material of this embodiment:
[0086] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0087] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.8 mm;
[0088] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0089] Performance Test:
[0090] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0091] Example 4
[0092] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0093] 15 parts of bismuth oxychloride, 5 parts of titanium dioxide, 0.3 parts of polycarboxylic acid sodium salt dispersant, 0.3 parts of mineral oil defoamer, 3 parts of zeolite stabilizer, 1.5 parts of acrylic thickener, and the rest is supplemented to 100 parts with deionized water.
[0094] Preparation method of the photocatalytic composite material of this embodiment:
[0095] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0096] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.9 mm;
[0097] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0098] Performance Testing:
[0099] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0100] Example 5
[0101] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0102] 10 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0.3 parts of polyacrylate ammonium salt dispersant, 0.4 parts of mixed defoamer, 1 part of clinoptilolite stabilizer, 0.5 parts of acrylic thickener, and the rest is supplemented to 100 parts with deionized water.
[0103] Preparation method of the photocatalytic composite material of this embodiment:
[0104] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0105] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.7 mm;
[0106] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0107] Performance Testing:
[0108] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0109] Example 6
[0110] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0111] 5 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0.1 parts of polycarboxylate sodium salt dispersant, 0.1 parts of mixed defoamer, 5 parts of zeolite stabilizer, 2 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0112] Preparation method of the photocatalytic composite material of this embodiment:
[0113] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0114] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.8 mm;
[0115] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0116] Performance Testing:
[0117] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0118] Example 7
[0119] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0120] 15 parts of bismuth oxychloride, 20 parts of titanium dioxide, 0.5 parts of polyacrylate ammonium salt dispersant, 0.5 parts of mixed defoamer, 5 parts of clinoptilolite stabilizer, 0.8 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0121] Preparation method of the photocatalytic composite material of this embodiment:
[0122] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0123] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 1.0 mm;
[0124] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0125] Performance Testing:
[0126] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0127] Example 8
[0128] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0129] 3 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0.5 parts of phosphate dispersant, 0.2 parts of silicone defoamer, 2 parts of zeolite stabilizer, 2 parts of acrylic thickener, and the rest is supplemented to 100 parts with deionized water.
[0130] Preparation method of the photocatalytic composite material of this embodiment:
[0131] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0132] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.7 mm;
[0133] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0134] Performance Testing:
[0135] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0136] Example 9
[0137] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0138] 10 parts of bismuth oxychloride, 20 parts of titanium dioxide, 0.2 parts of phosphate dispersant, 0.3 parts of mixed defoamer, 3 parts of clinoptilolite stabilizer, 0.2 parts of acrylic thickener, and the rest is supplemented to 100 parts with deionized water.
[0139] Preparation method of the photocatalytic composite material of this embodiment:
[0140] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0141] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.6 mm;
[0142] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0143] Performance Test:
[0144] The photocatalytic composite material prepared in this embodiment was subjected to performance tests, including tests on the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 viruses). The results are detailed in Table 1.
[0145] Example 10
[0146] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0147] 0.4 parts of polycarboxylate sodium salt dispersant, 0.3 parts of mineral oil defoamer, 0.4 parts of alkanolamine pH regulator, 0.2 parts of polyurethane thickener, 5 parts of photocatalytic composite slurry prepared in Example 6, 5 parts of diatomaceous earth, 25 parts of titanium dioxide, 5 parts of calcined kaolin, 5 parts of feldspar powder, 20 parts of acrylic emulsion, 0.5 parts of film-forming aid, and the rest is supplemented to 100 parts with deionized water.
[0148] Preparation method of the photocatalytic composite material coating of this embodiment:
[0149] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0150] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0151] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0152] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0153] Performance Test:
[0154] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0155] Embodiment 11
[0156] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0157] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH regulator, 0.3 parts of acrylic thickener, 10 parts of the photocatalytic composite slurry prepared in Example 6, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is made up to 100 parts with deionized water.
[0158] Preparation method of the photocatalytic composite material coating of this embodiment:
[0159] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0160] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0161] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0162] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0163] Performance Testing:
[0164] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0165] Example 12
[0166] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0167] 0.3 parts of polyacrylate ammonium salt dispersant, 0.4 parts of mineral oil defoamer, 0.2 parts of potassium alkyl silicon carboxylate pH regulator, 0.2 parts of polyurethane thickener, 15 parts of photocatalytic composite slurry prepared in Example 6, 1 part of diatomaceous earth, 5 parts of titanium dioxide, 10 parts of calcined kaolin, 1 part of feldspar powder, 15 parts of silicon-modified acrylic emulsion, 0.3 parts of film-forming aid, and the rest is made up to 100 parts with deionized water.
[0168] Preparation method of the photocatalytic composite material coating of this embodiment:
[0169] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0170] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0171] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0172] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0173] Performance Testing:
[0174] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0175] Comparative Example 1
[0176] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0177] 5 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0.1 parts of polycarboxylate sodium salt dispersant, 0.1 parts of mixed defoamer, 0 parts of zeolite stabilizer, 2 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0178] Preparation method of the photocatalytic composite material of this comparative example:
[0179] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0180] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.8 mm;
[0181] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0182] Performance Test:
[0183] The prepared photocatalytic composite materials were subjected to performance tests, including the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 1.
[0184] Comparative Example 2
[0185] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0186] 5 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0 parts of polycarboxylate sodium salt dispersant, 0.1 parts of mixed defoamer, 5 parts of zeolite stabilizer, 2 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0187] Preparation method of the photocatalytic composite material of this comparative example:
[0188] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture for 15 minutes at a speed of 600 rpm using a mechanical disperser to obtain an additive dispersion;
[0189] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 600 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the material and subjecting it to a high-speed shaking process for 1 hour. The mass ratio of the material before adding the zirconium beads to the mass of the zirconium beads is 1:1, and the size of the zirconium beads can be selected to be 0.8 mm;
[0190] (C) filtering the above solution using ash-free filter paper to remove the zirconium beads, collecting the filtrate to obtain a photocatalytic composite slurry; and finally obtaining a bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0191] Performance Test:
[0192] The prepared photocatalytic composite materials were subjected to performance tests, including the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 1.
[0193] Comparative Example 3
[0194] A photocatalytic composite material comprises the following raw material components in parts by weight:
[0195] 5 parts of bismuth oxychloride, 30 parts of titanium dioxide, 0.1 parts of polycarboxylate sodium salt dispersant, 0.1 parts of mixed defoamer, 5 parts of zeolite stabilizer, 2 parts of polyurethane thickener, and the rest is supplemented to 100 parts with deionized water.
[0196] Preparation method of the photocatalytic composite material of this embodiment:
[0197] (A) adding a dispersant, a defoamer, a stabilizer, and a thickener into deionized water, and stirring the mixture at a speed of 600 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion;
[0198] (B) adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, and stirring for 25 minutes at a speed of 1000 rpm by mechanical dispersion; finally obtaining bismuth oxychloride / titanium dioxide photocatalytic composite slurry.
[0199] Performance Test:
[0200] The prepared photocatalytic composite materials were subjected to performance tests, including the state in the container, pH, KU viscosity, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 1.
[0201] Comparative Example 4
[0202] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0203] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH regulator, 0.3 parts of acrylic thickener, 0 parts of photocatalytic composite slurry prepared in Example 6, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is made up to 100 parts with deionized water.
[0204] Preparation method of the photocatalytic composite material coating of this embodiment:
[0205] (A) adding a dispersant, a defoamer, a pH regulator, and a thickener to deionized water, and stirring the mixture at a speed of 600 rpm for 10 minutes by mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0206] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0207] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0208] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0209] Performance Test:
[0210] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0211] Comparative Example 5
[0212] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0213] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH adjuster, 0.3 parts of acrylic thickener, 3 parts of titanium dioxide, 0.5 parts of bismuth oxychloride, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is made up to 100 parts with deionized water.
[0214] Preparation method of the photocatalytic composite material coating of this embodiment:
[0215] (A) adding a dispersant, a defoamer, a pH regulator, and a thickener into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0216] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin, feldspar powder, titanium dioxide and bismuth oxychloride to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing a photocatalytic composite material;
[0217] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0218] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0219] Performance Test:
[0220] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0221] Comparative Example 6
[0222] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0223] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH regulator, 0.3 parts of acrylic thickener, 10 parts of photocatalytic composite slurry prepared in Comparative Example 1, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is supplemented to 100 parts with deionized water.
[0224] Preparation method of the photocatalytic composite material coating of this embodiment:
[0225] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0226] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0227] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0228] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0229] Performance Test:
[0230] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0231] Comparative Example 7
[0232] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0233] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH regulator, 0.3 parts of acrylic thickener, 10 parts of photocatalytic composite slurry prepared in Comparative Example 2, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is supplemented to 100 parts with deionized water.
[0234] Preparation method of the photocatalytic composite material coating of this embodiment:
[0235] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0236] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0237] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0238] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0239] Performance Testing:
[0240] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0241] Comparative Example 8
[0242] A photocatalytic composite material application coating comprises the following raw material components in parts by weight:
[0243] 0.3 parts of phosphate dispersant, 0.3 parts of silicone defoamer, 0.3 parts of ammonia pH regulator, 0.3 parts of acrylic thickener, 10 parts of photocatalytic composite slurry prepared in Comparative Example 3, 3 parts of diatomaceous earth, 15 parts of titanium dioxide, 8 parts of calcined kaolin, 3 parts of feldspar powder, 25 parts of styrene acrylic emulsion, 0.4 parts of film-forming aid, and the rest is supplemented to 100 parts with deionized water.
[0244] Preparation method of the photocatalytic composite material coating of this embodiment:
[0245] (A) adding a dispersant, a defoamer, a pH regulator, a thickener, and a photocatalytic composite slurry into deionized water, and stirring for 10 minutes at a speed of 600 rpm using mechanical dispersion to obtain a premixed solution of a photocatalytic composite material-auxiliary agent;
[0246] (B) adding diatomaceous earth, titanium dioxide, calcined kaolin and feldspar powder to the premixed solution, stirring for 15 minutes at a speed of 1500 rpm using mechanical dispersion to obtain a slurry containing the photocatalytic composite material;
[0247] (C) adding the emulsion and the film-forming aid to the slurry, stirring for 15 minutes at a speed of 600 rpm by mechanical dispersion, to obtain a preliminary finished coating;
[0248] (D) The above-mentioned preliminary finished coating product is filtered through a 150-mesh filter to remove impurities, and finally a coating of a photocatalytic composite material is obtained.
[0249] Performance Test:
[0250] The photocatalytic composite material prepared in this embodiment was applied to the coating for performance testing, including film state, fineness, pH, KU viscosity, QUV aging, dye degradation rate, formaldehyde purification efficiency, toluene purification efficiency, antibacterial rate (Escherichia coli and Staphylococcus aureus) and virus inactivation rate (H3N2 and EV71 virus) tests. The results are shown in Table 2.
[0251] Comparative example:
[0252] Comparative Example 1: Based on Example 6, no stabilizer zeolite is added;
[0253] Comparative Example 2: Based on Example 6, no dispersant was added;
[0254] Comparative Example 3: Based on Example 6, the formula remains unchanged, but the grinding preparation process only adopts a mechanical dispersion process; (that is, both Example 6 and Comparative Example 3 use a mechanical dispersion process, but Example 6 includes a mechanical dispersion + grinding process (that is, zirconium beads are added for the grinding process); the preparation process of Comparative Example 3 does not have a grinding process, but is only a pure mechanical dispersion process).
[0255] Comparative Example 4: Based on Example 11, the photocatalytic composite slurry prepared in Example 6 is not added;
[0256] Comparative Example 5: Based on Example 11, the photocatalytic composite slurry prepared in Example 6 was not added, and the photocatalytic materials (titanium dioxide and bismuth oxychloride) corresponding to the photocatalytic composite slurry were added instead;
[0257] Comparative Example 6: Based on Example 11, the photocatalytic composite slurry prepared in Example 6 was not added, and the photocatalytic composite slurry prepared in Comparative Example 1 was added instead;
[0258] Comparative Example 7: Based on Example 11, the photocatalytic composite slurry prepared in Example 6 was not added, and the photocatalytic composite slurry prepared in Comparative Example 2 was added instead;
[0259] Comparative Example 8: Based on Example 11, the photocatalytic composite slurry prepared in Example 6 was not added, and the photocatalytic composite slurry prepared in Comparative Example 3 was added instead.
[0260] The photocatalytic composite materials prepared in the above Examples 1 to 9 and Comparative Examples 1 to 3 were subjected to performance tests, with reference to the following standards: T / SICCA003-2018 "Photocatalysts for Indoor Air Purification", GB / T 30706 "Test methods and evaluation of antibacterial properties of photocatalytic antibacterial materials and products under visible light irradiation" and ISO 18071 "Determination of antiviral activity of semiconductor photocatalytic materials under indoor lighting environments". The results are shown in Table 1 below.
[0261] The photocatalytic composite materials prepared in the above embodiments 10 to 12 and comparative examples 4 to 8 were used for performance testing of coatings, with reference to the following standards: T / SICCA003-2018 "Photocatalysts for Indoor Air Purification", ASTM G154 "Standard Procedure for Fluorescent Ultraviolet Lamp Irradiation of Non-metallic Materials", GB / T 1766-2008 "Rating Method for Aging of Paint and Varnish Coatings", JC / T1074-2021 "Purification Performance of Indoor Air Purification Functional Coating Materials", GB / T 21866 "Determination of Antibacterial Properties and Antibacterial Effects of Antibacterial Coatings (Paint Films)", and China Coating Association Antiviral Coatings Standards (two standards, T / CNCIA 01014-2020 and T / CNCIA 03002-2020 test methods). The results are shown in Table 2 below.
[0262] On the basis of the photocatalytic composite material of Example 6, by controlling the single variable method, the stabilizer zeolite (corresponding to the corresponding proportion 1), the dispersant (corresponding to the corresponding proportion 2) and the preparation process (corresponding to the corresponding proportion 3) were deducted respectively, and the stability of the material was significantly reduced. After the material was placed for a long time, hard precipitation appeared. The photocatalytic performance (dye degradation rate), air purification function (including formaldehyde purification efficiency and toluene purification efficiency), antibacterial rate (including Escherichia coli and Staphylococcus aureus) and virus inactivation rate (including influenza virus H3N2 and anti-enterovirus EV71) of the material were all reduced;
[0263] On the basis of the photocatalytic composite material applied coating in Example 11, by controlling the single variable method, after the photocatalytic composite slurry prepared in Example 6 (corresponding to Example 4) is not added to the formula, the basic performance of the formula has no obvious abnormality, but the photocatalytic performance (dye degradation rate) of the coating is completely lost, and the air purification function (including formaldehyde purification efficiency and toluene purification efficiency), antibacterial rate (including Escherichia coli and Staphylococcus aureus) and virus inactivation rate (including influenza virus H3N2 and anti-enterovirus EV71) performance are significantly reduced;
[0264] Based on the application of photocatalytic composite materials to coatings in Example 11, by controlling the single variable method, the photocatalytic composite slurry prepared in Example 6 was not added in the formula, but the corresponding amount of photocatalytic materials titanium dioxide and bismuth oxychloride in the photocatalytic composite slurry was added (corresponding to Example 5), the photocatalytic composite slurry prepared in Example 6 was not added, but the photocatalytic composite slurry prepared in Comparative Example 1 was added (corresponding to Example 6), the photocatalytic composite slurry prepared in Example 6 was not added, but the photocatalytic composite slurry prepared in Comparative Example 2 was added (corresponding to Example 7), and the photocatalytic composite slurry prepared in Example 6 was not added, but the photocatalytic composite material prepared in Comparative Example 3 was added (corresponding to Example 8). The coating formulas prepared by the coating formulas all showed obvious The defects include the increase of formula fineness, particles and discoloration of the coating film; QUV aging results show that when the photocatalytic materials titanium dioxide and bismuth oxychloride are directly added to the formula, or the added photocatalytic composite slurry lacks key additives (such as stabilizers, dispersants) or the preparation process is changed to pure mechanical dispersion, the coatings will show discoloration and powdering defects to varying degrees; in addition, the photocatalytic performance (dye degradation rate) of the prepared coatings has been greatly reduced, and the air purification function (including formaldehyde purification efficiency and toluene purification efficiency), antibacterial rate (including Escherichia coli and Staphylococcus aureus) and virus inactivation rate (including influenza virus H3N2 and anti-enterovirus EV71) performance have all been significantly reduced.
[0265] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0266] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0267] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0268] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0269] Unless otherwise indicated, percentages and parts are by weight and by mass.
[0270] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0271] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
[0272] Table 1 Performance test results of Examples 1 to 9 and Comparative Examples 1 to 3
[0273]
[0274] Continued from the table above
[0275]
[0276]
[0277] Table 2 Performance test results of Examples 10 to 12 and Comparative Examples 4 to 8
[0278]
[0279] Continued from the table above
[0280]
[0281]
Claims
1. A photocatalytic composite material, characterized in that: The photocatalytic composite material comprises a bismuth oxychloride / titanium dioxide composition with a semiconductor-semiconductor staggered heterojunction.
2. The photocatalytic composite material according to claim 1, characterized in that: The bismuth oxychloride / titanium dioxide composition comprises the following components: Bismuth oxychloride, titanium dioxide, dispersant, defoamer, stabilizer, thickener and deionized water.
3. The photocatalytic composite material according to claim 2, characterized in that: The bismuth oxychloride / titanium dioxide composition comprises the following components in parts by weight: 1-30 parts of bismuth oxychloride, 1-30 parts of titanium dioxide, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of defoamer, 0.5-5 parts of stabilizer, 0.1-2 parts of thickener, and the rest is supplemented to 100 parts with deionized water.
4. The photocatalytic composite material according to claim 2, characterized in that: It includes the following features One or a combination of: The stabilizer is one or a combination of zeolite and clinoptilolite; the microstructure of the stabilizer is a nanorod structure with a width of 100 to 500 nm and a length of 200 nm to 5 μm; The dispersant is one or a combination of nonionic surfactants or anionic surfactants; The bismuth oxychloride is an ultra-thin nanosheet structure, and the thickness of the nanosheet is 5 to 100 nm; The crystal form of the titanium dioxide is anatase or rutile, and the particle size of the titanium dioxide is 2 to 50 nm.
5. The photocatalytic composite material according to claim 4, characterized in that: The stabilizer is one or a combination of zeolite and clinoptilolite; The microstructure of the stabilizer is a nanorod structure with a width of 200 to 400 nm and a length of 500 nm to 3 μm; The dispersant is one or a combination of polycarboxylic acid sodium salt, polyacrylate ammonium salt or phosphate ester; The bismuth oxychloride is an ultra-thin nanosheet structure, and the thickness of the nanosheet is 10 to 30 nm; The crystal form of the titanium dioxide is anatase or rutile, and the particle size of the titanium dioxide is 5 to 10 nm.
6. A method for preparing the photocatalytic composite material according to claim 2, characterized in that: It comprises the following preparation steps: A. Add dispersant, defoamer, stabilizer and thickener into deionized water, stir at a speed of 400-800 rpm for 15 minutes by mechanical dispersion to obtain an additive dispersion; B. adding bismuth oxychloride and titanium dioxide to the above-mentioned auxiliary agent dispersion, pre-stirring for 5 minutes at a speed of 400-800 rpm by mechanical dispersion, adding a certain mass of zirconium beads, transferring the materials and subjecting them to a high-speed shaking process for 0.5-2 hours; The mass ratio of the material before adding zirconium beads to the mass ratio of zirconium beads is selected between 1:1 and 1:5, and the size of the zirconium beads is selected between 0.6 and 1.0 mm; C. Filter the above solution using ash-free filter paper to remove the zirconium beads, collect the filtrate to obtain a photocatalytic composite slurry, and finally obtain a bismuth oxychloride / titanium dioxide composition with a semiconductor-semiconductor staggered heterojunction.
7. A coating, characterized in that: It comprises the photocatalytic composite material according to any one of claims 1 to 6.
8. Use of the photocatalytic composite material according to any one of claims 1 to 6 in air purification and / or antibacterial and / or antiviral.
9. Use of the coating according to claim 7 in air purification and / or antibacterial and / or antiviral applications.
Citation Information
Patent Citations
Preparation method of TiO2 / BiOCl nano photocatalyst powder
CN103464183A
Method for preparing powder-TiO2 photoinduced super-hydrophilic composite film at low temperature
CN105771952A
Antifouling self-cleaning coating and preparation method thereof
CN112920663A
MOF modified zeolite loaded BiOX / TiO2 photocatalytic material and preparation method thereof
CN113751033A
Cited By
Photocatalytic composite slurry, photocatalytic air purification exterior wall coating and preparation method of photocatalytic air purification exterior wall coating
CN121108796A